The Relationship Between Musical Accompaniment Learning Media and the Skills Learning Outcomes of Participants in Traditional Minangkabau Dance Training at Baiturrahmah Studio Padang City - Restu Putri; Jamaris Jamna (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the success of the Baiturrahmah Studio in carrying out training activities. This can be seen from the activeness of the training participants in participating in training activities and the large number of participants invited to major events. This is because the media used in the training activities use direct music accompaniment that is played by the musician. The purpose of this study was to determine the relationship between the musical accompaniment learning media and the learning outcomes of the training participants at the Baiturrahmah Studio, Padang City. This type of research is a quantitative study that deals with a population of 40 people. The sampling technique used a random sample per cluster which was taken as much as 75% of the population. The number of samples in this study were 30 people. The data collection technique used was the data collection technique used by the researcher in this study, namely a questionnaire, while the data collection tool used by the researcher was a list of statements. Data analysis techniques used percentages and product moments. The results of this study indicate that: (1) The learning media of musical accompaniment in the implementation of traditional dance training are in accordance with the objectives to be achieved, (2) The learning outcomes of participants in traditional dance training are high, (3) There is a significant relationship between the use of media. learning with the results of learning the skills of traditional dance training participants. The hope of this research is to keep using and increasing the use of music accompaniment learning media in the implementation of traditional dance training. Keywords: Training Success, Music Accompaniment Media